The Impact of Audit Committees and Chief Executive Officer Characteristics on Real Earnings Management - Stanley Sanders; Bernadia Linggar Yekti Nugraheni (Soegijapranata Catholic University, 2024)
Earnings management is an opportunistic behavior influenced by many factors. However, previous studies have not extensively investigated the impact of audit committee mechanisms and Chief Executive Officer (CEO) characteristics on real earnings management. This study aims to analyze the impact of audit committee mechanisms and CEO characteristics on real earnings management. The study utilizes secondary data from manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2022. The audit committee mechanism is proxied by using two measurements i.e. the number of audit committee meetings and the educational background of the audit committee, Meanwhile, CEO characteristics are proxied by the gender and the CEO's tenure. By applying multiple regression, this study finds that the number of audit committee meetings and CEO’s tenure have significant negative effects on real earnings management. Meanwhile, the background of the audit committee does not affect real earnings management. Interestingly, this study finds that male CEOs decrease real earnings management. Therefore, this research provides evidence that the number of audit committee meetings and CEO’s tenure play significant roles in reducing opportunistic behavior in a company.